Phase Behavior and Fuel Properties of Bio-Oil/Glycerol/Methanol Blends - Zhang, Mingming; Wu, Hongwei (American Chemical Society, 2014)
This study investigates the phase behavior and fuel properties of a series of bio-oil/glycerol/methanol blends. The results show that even though glycerol has a poor solubility in bio-oil, homogeneous bio-oil/glycerol/methanol fuel blends can be prepared with appropriate amount of methanol addition. Compared to the bio-oil or glycerol alone as a fuel, the bio-oil/glycerol/methanol blends have improved fuel properties (higher heating value, lower viscosity, and lower surface tension, etc.). Taking into safety consideration during storage and transportation of a fuel and the possible ratio of glycerol to methanol that may be obtained from biodiesel production process, potential feasible compositions of the bio-oil/glycerol/methanol blends (bio-oil ≥ 70 wt %; glycerol ≤ 20 wt %; methanol ≤ 10 wt %) are recommended as burner fuel for combustion applications. Further accelerated aging experiments of selected fuel blends in the recommended composition range indicate that the fuel blends experience decreases in the viscosity and total acid number and an increase in water content of the fuel blends upon long-term storage.